Satellite-to-ground radiowave propagation - Allnutt, J. E. (IET electromagnetic waves series ;, 2011)
The book is divided into eight chapters: radiowave Earth-space communications; ionospheric effects; clear-air effects; attenuation effects; depolarization effects; mobile satellite service propagation effects; optical communications propagation effects; and restoration of performance during signal impairments.